The Afterlives of Adam Scriveyn: Chaucer's Scribe in Dantes's Inferno - O'Connell, Brendan (My University, 2024)
This essay examines Adam Scriveyn, a short poem by Geoffrey Chaucer that explicitly addresses the vagaries of textual production, and whose critical history illustrates the unreliability of textual evidence, whether in the age of manuscript, print, or digital copies. The poem’s possible debt to Dante underscores the importance of thinking across different linguistic and literary traditions as we assess the contrasting evidence provided by textual witnesses. After considering how access to digital manuscripts of Dante can enrich our understanding of English literary traditions, I show that the afterlife of Adam Scriveyn, including its digital presence, foregrounds the challenges and opportunities presented by the widespread availability of digital copies of medieval manuscripts. Digital surrogates transform the ways we think about cultural contact, and prompt us to consider how technologies of textual production shape the questions we pose about literary and textual authority.
PUBLISHED
Keywords: Geoffrey Chaucer, Adam Scriveyn, Dante’s influence on English literature, Textual transmission, Digitised manuscripts; Manuscript, Book and Print Cultures; Chaucer; Dante's influence on English literature; Medieval manuscripts; Textual transmission